Atraumatic Pulsatile Leukocyte Circulation for Long‐Term In Vitro Dynamic Culture and Adhesion Assays. Issue 11 (20th April 2015) - Mazza, Giulia; Stoiber, Martin; Pfeiffer, Dagmar; Schima, Heinrich
Abstract Low flow rate pumping of cell suspensions finds current applications in bioreactors for short‐term dynamic cell culture and adhesion assays. The aim of this study was to develop an atraumatic pump and hemodynamically adapted test circuit to allow operating periods of at least several hours. A computer‐controlled mini‐pump (MP) was constructed based on non‐occlusive local compression of an elastic tube with commercial bi‐leaflet valves directing the pulsatile flow into a compliant circuit. Cell damage and activation in the system were tested with whole blood in comparison with a set with a conventional peristaltic pump (PP). Activation of circulating THP‐1 monocytes was tested by measuring the expression of CD54 (ICAM‐1). Additionally, monocyte‐endothelial interactions were monitored using a parallel‐plate flow chamber with an artificial stenosis. The system required a priming volume of only 20 mL, delivering a peak pulsatile flow of up to 35 mL/min. After 8 h, blood hemolysis was significantly lower for MP with 11 ± 3 mg/dL compared with PP with 100 ± 16 mg/dL. CD142 (tissue factor) expression on blood monocytes was 50% lower for MP. With MP, THP‐1 cells could be pumped for extended periods (17 h), with no enhanced expression of CD54 permitting the long‐term co‐culture of THP‐1 with endothelial cells and the analysis of flow pattern effects on cell adhesion. A low‐damage assay setup was developed, which allows the pulsatile flow of THP‐1 cells and investigation of their interaction with other cells or surfaces for extended periods of time.